Which shows the correct substitution of the values a, b, and c from the equation 0 = 4x2 + 2x – 1 into the quadratic formula below?

Quadratic formula: x =

Respuesta :

miriyu
0 = 4x² + 2x – 1

this equation is already ordered by degree, so it's in the correct form. the standard form of a parabola is like so: 0 = A
x² + Bx - C

that's exactly how you plug values into the quadratic formula. the coefficient for your squared value, A, is 4. take the coefficients from your other numbers as well.

a = 4
b = 2
c = -1

Answer:

[tex]x=\frac{-2\pm \sqrt{(2)^{2}-4(4)(-1)}}{2(4)}[/tex] is the answer.

Step-by-step explanation:

Given quadratic equation is 4x²+ 2x - 1 = 0

To find the solution of the equation we use the quadratic formula

[tex]x=\frac{-b\pm \sqrt{b^{2}-4ac}}{2a}[/tex]

Now we put the values of a = 4, b = 2 and c = (-1)

Therefore, quadratic formula for the equation given will be

[tex]x=\frac{-2\pm \sqrt{(2)^{2}-4(4)(-1)}}{2(4)}[/tex]